An Introduction to Data Everything You Need to Know About AI, Big Data and Data Science - Corea, Francesco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book reflects the author's years of hands-on experience as an academic and practitioner. It is primarily intended for executives, managers and practitioners who want to redefine the way they think about artificial intelligence (AI) and other exponential technologies. Accordingly the book, which is structured as a collection of largely self-contained articles, includes both general strategic reflections and detailed sector-specific information. More concretely, it shares insights into what it means to work with AI and how to do it more efficiently; what it means to hire a data scientist and what new roles there are in the field; how to use AI in specific industries such as finance or insurance; how AI interacts with other technologies such as blockchain; and, in closing, a review of the use of AI in venture capital, as well as a snapshot of acceleration programs for AI companies. .
Introduction to Data -- Big Data Management: How Organizations Create and Implement Data Strategies -- Introduction to Artificial Intelligence -- AI Knowledge Map: how to classify AI technologies -- Advancements in the field -- AI Business Models -- Hiring a data scientist -- AI and Speech Recognition -- AI and Insurance -- AI and Financial Services -- AI and Blockchain -- New roles in AI -- AI and Ethics -- AI and Intellectual Property -- AI and Venture Capital -- A guide to AI accelerators and incubators.
Keywords: Computational intelligence; Big data; Quantitative research; Artificial intelligence; Neural networks (Computer science) .; Computational Intelligence; Big Data; Data Analysis and Big Data; Artificial Intelligence; Mathematical Models of Cognitive Processes and Neural Networks